Reduced brain activity during a working memory task in middle-aged apolipoprotein E ε4 carriers with overweight/obesity - Drake, Jermon A.; Jakicic, John M.; Rogers, Renee J.; Aghjayan, Sarah L.; Stillman, Chelsea M.; Donofry, Shannon D.; Roecklein, Kathryn A.; Lang, Wei; Erickson, Kirk I. (Frontiers in Human Neuroscience, 2022)
Objective The apolipoprotein E ε4 (APOE ε4) allele and midlife obesity are independent risk factors for Alzheimer’s disease (AD). Both of these risk factors are also associated with differences in brain activation, as measured by blood oxygenation level-dependent (BOLD) responses, in the absence of detectable cognitive deficits. Although the presence of these risk factors may influence brain activity during working memory tasks, no study to date has examined whether the presence of the ε4 allele explains variation in working memory brain activity while matching for levels of overweight/obesity. The primary aim of this study was to determine whether the presence of the ε4 allele is associated with differences in task-functional magnetic resonance imaging (fMRI) brain activation in adults with overweight/obesity. We predicted that ε4 carriers would have greater brain activation in regions that support working memory. Methods This ancillary study included 48 (n = 24 APOE ε4 carriers; n = 24 APOE ε4 non-carriers), sedentary middle-aged adults (Mean age = 44.63 ± 8.36 years) with overweight/obesity (Mean BMI = 32.43 ± 4.12 kg/m2) who were matched on demographic characteristics. Participants were a subsample enrolled in 12-month randomized clinical trial examining the impact of energy-restricted diet and exercise on cardiovascular health outcomes. Participants completed a n-back working memory task with fMRI, which were completed within one month of the start of the intervention. Participants also underwent pseudo-continuous arterial spin labeling scans, a MRI measure of cerebral blood flow (CBF). Results Compared to non-ε4 carriers with overweight/obesity, ε4 carriers with overweight/obesity had lower fMRI brain activity in the middle frontal gyrus, pre and post central gyrus, supramarginal gyrus, superior temporal gyrus, lateral occipital cortex, and angular gyrus (z range = 2.52–3.56) during the n-back working memory task. Differences persisted even when controlling for CBF in these brain regions. Conclusion These results indicate that presence of the APOE ε4 allele in middle-aged adults with overweight/obesity is related to altered brain activity during a working memory paradigm, which may confer risk for accelerated neurocognitive decline in late adulthood. Future research is needed to clarify the clinical implications of these findings in the context of risk for AD.